Ответы и объяснения

2014-02-17T04:31:34+00:00
1) (x-1)(x^2+1)(x+1)=(x^2-1)(x^2+1)=x^4-1
f '(x)=(x^4-1)'=4x^3; f '(x)=0; 4x^3=0; x=0
2) f '(x)=3x^2-12x; g '(x)=1/3 *(1/(2coren x)=1/(6coren x)
f '(x)-g'(x)=0; 3x^2-12x-1/(6(coren x))=0
3)f '(x)=(2/3)*(3x^2)=2x^2; g '(x)=2*(1/(2coren x))=1/coren x
((2x^2)/(1/coren x)=0; 2x^2 *(coren x)=0: x=0

4) f '=3x^2; f'(x)-f(x)=3x^2-x^3; 3x^2-x^3=0; x^2(3-x)=0; x=0 ; x=3 Ответ. 0;3.
Комментарий удален
2x-(6x-4)=0; -4x+4=0; -4x=-4; x=1
6) f '=2x; g'=4x-3+4(x+1)=8x+1; 2x=8x+1; 6x=-1; x=-1/6
11) f '(x)=2x(x-1)^2+2(x-1)*x^2-6(x+1+6x)=2x^3-4x+2x+2x^3-2x^2-12x-6;2x^3-4x+2x+2x^3-2x^2-12x-6=-18; 4x^3-14x-2x^2+12=0; 2x^3--x^2-7x+6=0; (x-1)(2x^2+x--6=0;......... x=1;(этот угадываем, затем делим на (х-1), получим квадратное уравнение) x=-2; x=1,5 Ответ-2;1;1,5.